"A senhora não está conseguindo dar conta do meu filho?": discursividades de professores de uma escola pública de São Paulo - Ferraz, Marcel Amaral Marques (2019)
The discourse is crossed by the ideology and the unconscious that cause the subject and precedes it. The right one feeds the mistake of being the author of his own speech, however he is being crossed by ideologies that speaks for him, because the discursiveness comes before the subject. If the subject does not exist out of the ideology, what is left for him to reflect how it acts upon his relations, depending on the subjective position occupied. Based on this precept and, concerned about the high levels of school dropout and illiteracy, we decided to explore this field. The goal of the current research consisted to interfere on the discourse of teachers and then, analyze the discursiveness that crosses their speech about the relationship between them and the students. Material and method: it is an interventional type research, developed with teachers from a public school in São Paulo. Having as support the Conversation Method, interventional supply proposed by J-A Miller, researchers interacted with teachers and recorded, transcribed, and took notes of the meetings. The collected material composes the corpus, and for the analysis, it was chosen the reading device offered by the Discourse Analysis (DA), begotten by Michel Pêcheux. Results: it is possible to infer that the discursiveness uttered by the teachers puts students in a position that does not define them, but makes them objects of desire for the teacher, resulting the vanishing of their subjectivity, against the impossibility of being the desiring subject. There is a resistance from the teachers to make contact with who the students really are. Therefore, the relationship is based on the teacher’s imaginary, who believes the students meant to be this or that way in order to learn. The teachers have kept imagetically fixed on the ideal of a perfect student, making impossible the teaching and learning process. Some of the displacements were provoked by the interventions, when the teachers could consider themselves fallible on their relationship with the students, who were, at the beginning, the guilty for the school failure. The teachers realized an effort of reflection in favor of the approximation with the students, still with remnants of totalizing discursiveness. It is possible to solve some of the conflicts among teachers and students, depending on a level of symbolic resources that not all teachers have. However, we can observe that teachers are able to solve this conflict, by taking the responsibility for their relationship with students. This manifestation can be understood as a taking back of their position of teacher, invaded by professionals from other areas, who put themselves as masters of an educational knowledge supposedly unknown by the teachers